Sociocultural perspectives on suicidal behaviour at the Coast Region of Kenya: an exploratory qualitative study - Ongeri, L; Nyawira, M; Kariuki, SM; Theuri, C; Bitta, M; Penninx, B; Newton, CR; Tijdink, J (BMJ Publishing Group, 2022)
Objectives To explore perceived sociocultural factors that may influence suicidality from key informants residing in coastal Kenya. Design We used an exploratory qualitative study design. Setting Mombasa and Kilifi Counties of Coastal Kenya. Participants 25 key informants including community leaders, professionals and community members directly and indirectly affected by suicidality. Methods We conducted in-depth interviews with purposively selected key informants to collect data on sociocultural perspectives of suicide. Thematic analysis was used to identify key themes using both inductive and deductive processes.